Artificial intelligence in higher education, opportunities, and challenges: a review - AlBlooshi, Sharifa (Frontiers in Education, 2026)
Artificial intelligence (AI) is a growing force of change in higher education, providing assistance to students, teachers, and administrators in teaching, learning, and administration. As AI technologies advance rapidly, they present a combination of significant opportunities and complex challenges. In this study, we examine the role of AI in higher education, highlighting both its positive and negative impacts, as well as current policy gaps and issues arising from its deployment. The literature on the topic was reviewed to determine how AI decisively impacts teaching and learning, the role of AI in assessments and academic integrity, as well as ethics, psychological considerations, and institutional governance from an ethical and psychological perspective. Technologies used in new areas, such as adaptive AI-based systems, intelligent tutoring platforms, and generative AI tools, create new opportunities for accessibility and personalization of learning experiences, thereby increasing student motivation. Skills development, such as writing and linguistic skills, can enhance AI capabilities. Additionally, it facilitates assessment methods by improving processes, providing immediate feedback, and adjusting evaluations accordingly. However, when students rely heavily on AI for their assessment tasks, it raises questions about academic integrity, cognitive offloading, and the limits of skills acquisition. While progress has been made, numerous open questions remain regarding the detection of AI-generated content, including the incorporation of fake narratives into generative AI tools, biases, privacy concerns, and the impact of the technology on our environment. Policies on AI governance have not yet matured in many higher education institutions; an integrated approach will be required from a broader perspective, including training faculty and utilizing institutional resources to benefit from AI while mitigating associated risks. To synthesize recent research on artificial intelligence in higher education, this study employs a narrative review approach. Unlike existing reviews that focus primarily on the integrated analysis of AI’s pedagogical, assessment, ethical, psychological, and institutional governance implications, this multidimensional perspective provides a consolidated framework to support responsible AI use across higher education systems.